2017
DOI: 10.1016/j.biocontrol.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity of Aphelinus species considered for introduction to control Diuraphis noxia

Abstract: Diuraphis noxia, the Russian wheat aphid, has become a major pest of wheat and barley since first being detected in the western USA in 1986. However, it is rarely a pest in Eurasia, its area of origin, and research has shown that natural enemies can limit its abundance there. Among the most important of natural enemies of D. noxia in Eurasia are parasitoids in the genus Aphelinus. Here we report results on host specificity of ten populations of seven species from two species complexes in the genus Aphelinus. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…If feeding on host hemolymph, females insert the ovipositor for about five min, which usually leads to quick host death. In contrast, an oviposition sting lasts about one min (Hopper, Lanier, Rhoades, Coutinot, et al, 2017). To control for host feeding, only aphids stung for less than one min were selected as replicates.…”
Section: Methodsmentioning
confidence: 99%
“…If feeding on host hemolymph, females insert the ovipositor for about five min, which usually leads to quick host death. In contrast, an oviposition sting lasts about one min (Hopper, Lanier, Rhoades, Coutinot, et al, 2017). To control for host feeding, only aphids stung for less than one min were selected as replicates.…”
Section: Methodsmentioning
confidence: 99%
“…However, A . certus was determined to be an unsuitable classical biological control agent because it parasitized a broad range of aphid species during tests in quarantine [29, 30]. In or before 2005, A .…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, Hopper et al . () demonstrated that A. varipes does not attack D. noxia , unlike A. hordei , which has established on R. padi and R. maidis within Australia (Waterhouse & Sands ).…”
Section: Managementmentioning
confidence: 99%